Self-rated sleep quality and mood states of Brazilian fighters - Bevilacqua G.G.* (2019)
© 2019 Universidad de León.Sleep has a direct relationship with mood. In this context, the aim of this study was to analyze the relationship between sleep quality and mood of combat sport athletes. A total of 188 elite male combat sports athletes participated in the study. Athletes who reported good sleep have greater vigor during competition than athletes with regular sleep and the mood profile was similar to the Iceberg Profile. In conclusion, there are relationships between sleep quality and mood of combat sport athletes, and athletes with good sleep quality present a mood profile nearest to the ideal for the best performance.